A Horse of a Different Color: Specifying With Precision Infants’ Mappings of Novel Nouns and Adjectives - Booth, Amy E. (2009)
A precisely controlled automated procedure confirms a developmental decalage: infants acquiring English link count nouns to object categories well before they link adjectives to properties. Fourteen- and 18-month-olds (n = 48 at each age) extended novel words presented as count nouns based on category membership, rather than shared properties. When the same words were presented as adjectives, infants revealed no preference for either category- or property-based extensions. The convergence between performance in this automated procedure and in more interactive tasks is striking. Perhaps more importantly, the automated task provides a methodological foundation for (1) exploring the development of form-meaning links in infants acquiring languages other than English, and (2) investigating the time-course underlying infants’ mapping of novel words to meaning.